MISKONSEPSI SISWA BIOLOGI TENTANG MATERI SISTEM RESPIRASI PADA SMA NEGERI SE-KABUPATEN LABUHANBATU - Nurhakima Ritonga; Halimah Sakdiah Boru Gultom; Novi Fitriandika Sari (Universitas Negeri Medan, 2018)
This study aims to analyze student misconception about the respiratory system material in SMA Negeri as Labuhanbatu District and to identify whether there is misconception. This research was conducted in SMA Negeri as Labuhanbatu Regency. The population in this study is all students of SMA Negeri in Labuhanbatu District, by using diagnostic test. The results showed that misconception occurred in students. The results of the analysis to show that the misconception of the students on the respiratory material, on the concept of respiration in the concept of human respiratory equipment (K2), the concept of gas exchange (K4), the concept of abnormalities and diseases of the human respiratory system (K 5) concept of the invertebrate animal (insect) (K 6) respiratory system. Based on the findings can be analyzed misconceptions on the students of the respiratory material identified misconception on the whole concept and need to improve the concept of teacher knowledge through training so that teachers can help students in understanding the concept so as to avoid the occurrence of misconception.Keywords: Misconception, Respiration, Biology’s Student